How the First Year of COVID-19 Affected Elective Pediatric Urology Patients: A Longitudinal Study Based on Waiting Lists and Surveys From 10 European Centers - Juul, Nikolai; Cazals, Aurélie; Hofmann, Aybike; Amesty, Virginia; Verkauskas, Gilvydas; Dobrowolska-Glazar, Barbara; Holmdahl, Gundela; Escolino, Maria; Birraux, Jacques; Kovacs, Tamas; Kalfa, Nicolas; Fossum, Magdalena (Frontiers in Public Health, 2022)
Introduction: COVID-19 impacted healthcare systems worldwide, and elective surgical activity was brought to a minimum. Although children were not primarily affected by the disease, pediatric urology was halted by clinical closedown and staff allocation. We aimed to document how these prioritizations affected waiting lists, and to investigate how European centers dealt with the challenge of these logistical and financial prioritizations. Materials and methods: This was a 1-year prospective study, starting March 2020. Participants were surveyed at three-month intervals about waiting lists for several common procedures as well as OR capacity and funding. Further, centers retrospectively reported on surgical and outpatient activity rates during 2019-2021. Waiting list tendencies were evaluated in relation to study baseline. Results: A marked decrease in surgical and outpatient activity was seen in the spring of 2020. Some included pediatric urology centers were able to increase their budget (15%) and staff working hours (20%) during part of the study period. Still, at the end of the study, the centers had increased the total number of patients on waiting lists with 11%, whereas the average days on waiting lists had accumulated with 73%, yielding a total of 6102 accumulated waiting days in the study population. Centers with decreased resources had markedly negative effects on waiting lists. Conclusions: Correlations between COVID-19 derived burdening of healthcare systems and the availability of pediatric urology greatly depends on the prioritizations made at individual centers. Ongoing monitoring of these correlations is warranted to safely avoid unnecessary negative impact on the pediatric population.